Accuracy of Fractional Flow Reserve Derived From Coronary Angiography. Issue 4 (22nd January 2019) - Fearon, William F.; Achenbach, Stephan; Engstrom, Thomas; Assali, Abid; Shlofmitz, Richard; Jeremias, Allen; Fournier, Stephane; Kirtane, Ajay J.; Kornowski, Ran; Greenberg, Gabriel; Jubeh, Rami; Kolansky, Daniel M.; et al.
Abstract : Background: Measuring fractional flow reserve (FFR) with a pressure wire remains underutilized because of the invasiveness of guide wire placement or the need for a hyperemic stimulus. FFR derived from routine coronary angiography (FFRangio ) eliminates both of these requirements and displays FFR values of the entire coronary tree. The FFRangio Accuracy versus Standard FFR (FAST-FFR) study is a prospective, multicenter, international trial with the primary goal of determining the accuracy of FFRangio . Methods: Coronary angiography was performed in a routine fashion in patients with suspected coronary artery disease. FFR was measured in vessels with coronary lesions of varying severity using a coronary pressure wire and hyperemic stimulus. Based on angiograms of the respective arteries acquired in ≥2 different projections, on-site operators blinded to FFR then calculated FFRangio using proprietary software. Coprimary end points were the sensitivity and specificity of the dichotomously scored FFRangio for predicting pressure wire–derived FFR using a cutoff value of 0.80. The study was powered to meet prespecified performance goals for sensitivity and specificity. Results: Ten centers in the United States, Europe, and Israel enrolled a total of 301 subjects and 319 vessels meeting inclusion/exclusion criteria which were included in the final analysis. The mean FFR was 0.81 and 43% of vessels had an FFR⩽0.80. The per-vessel sensitivity and specificity were 94% (95% CI, 88% to 97%) and 91% (86% to 95%), respectively, both of which exceeded the prespecified performance goals. The diagnostic accuracy of FFRangio was 92% overall and remained high when only considering FFR values between 0.75 to 0.85 (87%). FFRangio values correlated well with FFR measurements ( r =0.80, P <0.001) and the Bland–Altman 95% confidence limits were between −0.14 and 0.12. The device success rate for FFRangio was 99%. Conclusions: FFRangio measured from the coronary angiogram alone has a high sensitivity, specificity, and accuracy compared with pressure wire–derived FFR. FFRangio has the promise to substantially increase physiological coronary lesion assessment in the catheterization laboratory, thereby potentially leading to improved patient outcomes. Clinical Trial Registration: URL:https://www.clinicaltrials.gov . Unique Identifier: NCT03226262. Abstract : Supplemental Digital Content is available in the text.